Romanian Foreign Trade - a Regional Perspective - Gabriela Carmen Pascariu; Ramona Frunza; Anca Stângaciu (CES Working Papers, 2010)
The increasing integration of Romania in the global economy is a reality of the last years, proved through a constant growth of the foreign trade with other countries, which exceeded, in terms ofdynamics, both GDP and industrial production. In the first part of our paper, we intend to analyze the evolution of Romanian foreign trade in the period 1995-2007, focusing on the proportions of the imports and exports, at regional level. We wish to emphasize the correlations between the indicators that describe the degree of openness to foreign trade and indicators of competitiveness and specialization in different industries. The main goal of our approach is to highlight the sectors which generate comparative advantages and potential competitiveness poles, contributing significantly to the increase of the Romanian economy, expressed in GDP/capita. In the second part of the paper, based on the frame of analysis and interpretation defined and implemented in the first part, we intend to establish if the agglomeration processes in some regions of ourcountry will lead gradually to the strengthening of growth poles and, therefore to boost the foreign trade.
Keywords: 330; foreign trade; regional specialization; openness degree; comparative advantage; competitiveness